Does magnitude of deformity correlate with functional outcome following closed reduction in unilateral condylar fracture? - Nabil Syed; Nazimi Abdul Jabar (EDP Sciences, 2021)
Introduction: Condyle fracture can be treated surgically (ORIF) or conservatively (CTR). When treated by CTR, the fracture might not heal in a morphologically ideal shape. The severity of the deformity and its effects on the functional outcome is not known. This study would investigate the anatomical outcome of CTR and its effect on the functional outcome. Methods: Using a cross-sectional study design, we enrolled patients identified from our trauma census that meets the pre-determined inclusion criteria. Patient underwent assessment which involves clinical and radiographic evaluation. Clinical examination was done by using Helkimo Index. Radiographic evaluation by using cone beam computed tomography (CBCT) scan were traced and digitized, and the position and morphology of the fractured mandibular condyle was measured and compared with those of the contralateral non-fractured condyle in the axial, coronal and sagittal planes. Radiographic data was then compared with data from clinical examination. Results: 25 patients with unilateral condyle fracture and met the inclusion criteria were identified. Eight patients were successfully recalled and included in the study. Assessment was done on average of 40 months post-treatment. Clinical assessment with Helkimo Index showed that 63% had at least mild temporomandibular symptoms or dysfunction. CBCT examinations revealed that most patients had morphologically deformed healed condyle. No pattern can be seen in the magnitude of deformity with functional outcome. Conclusions: Following CTR, condyle fracture would heal in a morphologically deformed shape. Satisfactory functional outcome is still attainable despite this. The magnitude of the deformity does not appear to influence the functional outcome.